2017
DOI: 10.14710/jkt.v20i2.1698
|View full text |Cite
|
Sign up to set email alerts
|

Determinasi Bakteri Simbion Luminesensi Cumi Loligo edulis Serta Analisis Potensinya Sebagai Anti Bakteri

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Tannin compounds in the natural pigment of Rhizopora mucronata [11]. Moreover, found that the red pigment in Rhizopora mucronata was an indication of flavonoids and quinone contents and that the greenish black color showed tannin content in the species [10].…”
Section: Dyeing Using a Marina And B Gymnorrhiza Natural Dyementioning
confidence: 94%
See 3 more Smart Citations
“…Tannin compounds in the natural pigment of Rhizopora mucronata [11]. Moreover, found that the red pigment in Rhizopora mucronata was an indication of flavonoids and quinone contents and that the greenish black color showed tannin content in the species [10].…”
Section: Dyeing Using a Marina And B Gymnorrhiza Natural Dyementioning
confidence: 94%
“…Each sample weighing 100 grams was boiled in 1000 mL of clean water. Boiling was carried out at 90 0 C to concentrate the pigment, then stirred regularly for 1 h [10]. Batik Painting and Dyeing and dye binding as well as nglorod (The process of removing wax from painted Batik fabric) was carried out according to [11].…”
Section: Natural Dye Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kepadatan sel bakteri ini didukung oleh bentuk struktur lumen yang berlipat-lipat, sehingga menambah luas permukaaan lumen sebagai tempat koloni bakteri berkembang. Muara saluran bersilia juga dapat dijumpai sel-sel bakteri yang sama dengan sel bakteri dalam katung organ cahaya, hal ini menandakan bahwa saluran bersilia tersebut adalah merupakan saluran yang menghubungkan kantung organ cahaya dan bagian luar kantung (permukaan luar kantung tinta) (Pringgenies et al, 2017). Disamping itu, ada kemungkinan silia juga berperan dalam proses pengeluaran sebagian populasi sel-sel bakteri secara periodik yang kemudian digantikan oleh sel-sel dari hasil pembelahan yang baru, dengan demikian populasi sel bakteri selalu terjamin kemampuannya dalam proses pencahayaan.…”
Section: Lapisan Pigmen Organ Cahayaunclassified